Control interno y su relación con la gestión adiministrativa de la empresa hacienda“El Rosario”, cantón Valencia, año 2014 - Troya De La Rosa, Wendy Raquel (2016)
The research was conducted at the Hacienda "El Rosario" Valencia Canton, 2014 located on Avenue Dec. 13 to three hundred meters from the Service Station Valencia, whose overall objective is to evaluate the internal control and its relation to administrative management "Hacienda El Rosario" of the city of Valencia in 2014; research methods employed in internal control is performed inductive, deductive, scientific, analytical, synthetic and descriptive types of documentary and field research was also used; the primary techniques that helped meet the results were observation, interview and survey. Preliminary study: the format established for an audit, established comprising four phases was used. Planning, Implementation and Audit Report; the conclusions of which are also specified: Assessing Internal Control made the Hacienda "El Rosario" allowed analyzing IAS 41 and thus meet compliance with the administrative processes which perform day to day; demonstrating itself that workers of Hacienda perform their duties efficiently and effectively, in terms of administration demonstrate not lose objectivity in everything they do according to their established area; Referring to the deep assessment of internal controls Hacienda El Rosario was achieved assess the level of effectiveness of administrative processes by applying the components of COSO I system among which were: control environment, control activities, evaluation risk, information communication, supervision and monitoring, which demonstrated maintain excellent controls in the administration of the Hacienda el Rosario, obtaining a confidence level of 86% (ALTA) and a risk level of 14% (LOW) and a risk audit of 0.455% seeing it as acceptable; Administrative Management Hacienda El Rosario is poor because the evaluation system of internal controls, the absence of procedures to have a higher efficiency at departmental level was identified, the administration lacks implement improvements aimed at the Department of Human Talent to regulate and evaluate the performance of personnel, the application of efficiency indicator showed 25% of conflict in the administrative area; in 4% efficiency not archived document; the level of training with 37% of trainings that were not performed.